Commercial integrated library systems used in selected academic and special libraries - Esposo, Sharon Ma. S. 1964- (1999)
All the respondents said their expectations on the integrated library system were met. The system has performed as expected. Almost all of the respondents were satisfied with the integrated library system. Only one was not satisfied with the system currently used in their library.